ASSESSMENT OF THE LEVEL OF DEVELOPMENT OF THE ECONOMY AND INDUSTRY USING THE CRITERION OF ECONOMIC LEVEL OF TECHNOLOGIES - A. G. Zhivotovskaia (Вестник университета)
The indicator of evaluation of economic and technological quality of micro-, mesoand macro-level economic systems – economic level of technologies (ELT) has been considered. It reflects the efficiency of the main factors of production: labor and capital. A higher value of ELT is associated with greater economic and technological efficiency of the system, so it can be used as an indicator of the quality of the system. By graphical and econometric analysis, the values and trends of changes in the economic level of technologies at the level of economy and industry for five countries have been estimated: the Great Britain, Germany, Russia, the USA, France. The ability of the economic level of technologies to predict internal crises in the country has been considered. It has been proposed to use the economic level of technologies as a tool for forecasting as well as for planning and management.